TERORISME, PURITANISME DAN NEGARA - Ihsan, Soffa (Jurnal Review Politik, 2014)
This article attempts to give a literature description of the puritan movement and terrorismand how the state plays its role to cope withthese issues. Puritanism is characterized by a closed, absolutist, and literalattitude. Islam is kept out of the context of its historical aspects. The most prominent feature is a militant attitude of its followers by practicing the Islamic teachings offensively in which these often result in violent actions. A number model of Islamic groups like Salafi-Wahabi, for an instance, is spreading its dakwahvigorouslyand making a frequent friction among Muslim society in Indonesia. This fact goes along with terrorism. Some radical-terrorist cells continue to develop their power, while at the same they spreadsuch labelsas thaghut, kafir and syirik against other people.In this stage, the community along withthe state deal with face to face against radical ideology. Democracy is facing a dilemma in dealing with the radical movements. The writer argues, therefore, that there is a critical need to strengthen a moderate understanding and state’s firmness to regulateany religious ideology.